Physical and mechanical properties of ghora neem (Melia azedarach) plywood (Bangladesh Journal of Scientific and Industrial Research, 2014)
This paper gives the results of ghora neem (Melia azedarach) plywood for assessing it as an alternative raw material for plywood industries. Five ply ghora neem plywood of 2400 mm×1200 mm×12 mm size was manufactured using urea formaldehyde adhesive. The important physical and mechanical properties were examined for assessing its quality. The results of physical and mechanical properties of ghora neem plywood were compared with the data obtained with existing market available plywood manufactured with shimul (Bombax ceiba). The density of ghora neem plywood and shimul plywood was 541.00 and 499.80 kg/m3 respectively. The MOR was 58.33 N/mm2 for ghora neem plywood while it was 32.52 N/mm2 for the shimul plywood. The MOE was found for ghora neem plywood 3950.01 N/mm2 and on the other hand, the shimul plywood showed 3224.15 N/mm2. The ghora neem plywood showed better performance for both physical and mechanical properties and it also follows the standard. DOI: http://dx.doi.org/10.3329/bjsir.v49i1.18855 Bangladesh J. Sci. Ind. Res. 49(1), 47-52, 2014